Diabetes status-related differences in risk factors and mediators of heart failure in the general population: results from the MORGAM/BiomarCaRE consortium - Vuori Matti A.; Reinikainen Jaakko; Söderberg Stefan; Bergdahl Ellinor; Jousilahti Pekka; Tunstall-Pedoe Hugh; Zeller Tanja; Westermann Dirk; Sans Susana; Linneberg Allan; Iacoviello Licia; Costanzo Simona; et al. (BMC, 2025)
Background: The risk of heart failure among diabetic individuals is high, even under tight glycemic control. The correlates and mediators of heart failure risk in individuals with diabetes need more elucidation in large population-based cohorts with long follow-up times and a wide panel of biologically relevant biomarkers.
Methods: In a population-based sample of 3834 diabetic and 90,177 non-diabetic individuals, proportional hazards models and mediation analysis were used to assess the relation of conventional heart failure risk factors and biomarkers with incident heart failure.
Results: Over a median follow-up of 13.8 years, a total of 652 (17.0%) and 5524 (6.1%) cases of incident heart failure were observed in participants with and without diabetes, respectively. 51.4% were women and the mean age at baseline was 48.7 (standard deviation [SD] 12.5) years. The multivariable-adjusted hazard ratio (HR) for heart failure among diabetic individuals was 2.70 (95% confidence interval, 2.49-2.93) compared to non-diabetic participants. In the multivariable-adjusted Cox models, conventional cardiovascular disease risk factors, such as smoking (diabetes: HR 2.07 [1.59-2.69]; non-diabetes: HR 1.85 [1.68-2.02]), BMI (diabetes: HR 1.30 [1.18-1.42]; non-diabetes: HR 1.40 [1.35-1.47]), baseline myocardial infarction (diabetes: HR 2.06 [1.55-2.75]; non-diabetes: HR 2.86 [2.50-3.28]), and baseline atrial fibrillation (diabetes: HR 1.51 [0.82-2.80]; non-diabetes: HR 2.97 [2.21-4.00]) had the strongest associations with incident heart failure. In addition, biomarkers for cardiac strain (represented by nT-proBNP, diabetes: HR 1.26 [1.19-1.34]; non-diabetes: HR 1.43 [1.39-1.47]), myocardial injury (hs-TnI, diabetes: HR 1.10 [1.04-1.16]; non-diabetes: HR 1.13 [1.10-1.16]), and inflammation (hs-CRP, diabetes: HR 1.13 [1.03-1.24]; non-diabetes: HR 1.29 [1.25-1.34]) were also associated with incident heart failure. In general, all these associations were equally strong in non-diabetic and diabetic individuals. However, the strongest mediators of heart failure in diabetes were the direct effect of diabetes status itself (relative effect share 43.1% [33.9-52.3] and indirect effects (effect share 56.9% [47.7-66.1]) mediated by obesity (BMI, 13.2% [10.3-16.2]), cardiac strain/volume overload (nT-proBNP, 8.4% [-0.7-17.4]), and hyperglycemia (glucose, 12.0% [4.2-19.9]).
Conclusions: The findings suggest that the main mediators of heart failure in diabetes are obesity, hyperglycemia, and cardiac strain/volume overload. Conventional cardiovascular risk factors are strongly related to incident heart failure, but these associations are not stronger in diabetic than in non-diabetic individuals. Active measurement of relevant biomarkers could potentially be used to improve prevention and prediction of heart failure in high-risk diabetic patients.